Analisis Nilai Tambah Produk Olahan Buah Salak pada Usaha Mikro Kecil Menengah (UMKM) di Kecamatan Sukoharjo Kabupaten Wonosobo - Nugraeni, Violita; Kadarwati, Nunik; Alfarisy, M. Farid (Lingka Ekonomika, 2022)
One of the original fruit commodities from Indonesia is salak fruit. Salak is a horticultural commodity that is easily damaged, therefore it needs post-harvest handling so that salak fruit could have a longer shelf life. Salak can be processed into various products after going through processing. The purpose of this research is to 1) Know the added value generated by the salak fruit processing business 2) Know the profits generated from the salak fruit processing business 3) Know the business efficiency of the salak processing business in Sukoharjo district, Wonosobo Regency. The analytical tool used in this research is the Hayami Method. The result showed that 1) The added value of all salak fruit processing businesses obtained positive results and the most significant added value was obtained from salak dodol products, which was Rp 69.171,24/kg 2) All of the salak fruit processing businesses earn a profit and the biggest profit is obtained from the salak dodol product, which is Rp 62.504,57/kg 3) The calculation of the value of the business efficiency with the R/C ratio shows that all the salak fruit processing businesses get results <1 which means that all the salak fruit processing businesses are efficient and feasible to run.